A one-pot synthesis of 1, 6, 9, 13-tetraoxadispiro(4.2.4.2)tetradecane by hydrodeoxygenation of xylose using a palladium catalyst. (2nd September 2016) - Jackson, Michael A.; Blackburn, Judith A.; Price, Neil P.J.; Vermillion, Karl E.; Peterson, Steven C.; Ferrence, Gregory M.
Abstract: In an effort to expand the number of biobased chemicals available from sugars, xylose has been converted to 1, 6, 9, 13-tetraoxadispiro(4.2.4.2)tetradecane in a one-pot reaction using palladium supported on silica-alumina as the catalyst. The title compound is produced in 35–40% yield under 7 MPa H2 pressure at 733 K using 3–10 wt%Pd on silica-alumina catalyst. It is isolated using a combination of liquid-liquid extractions and flash chromatography. This dimer can be converted to its monomer, 2-hydroxy-(2-hydroxymethyl)tetrahydrofuran, which ring opens under acid conditions to 1, 5-dihydroxy-2-pentanone. This diol can then be esterified with vinylacetate in phosphate buffer to produce 1, 5-bis(acetyloxy)-2-pentanone which is an inhibitor of mammalian 11β-hydroxysteroid dehydrogenase 1. 1 H and 13 C nmr spectra of each of these species are reported. The single crystal X-ray structure of the title compound is also reported. These data were collected in a temperature range of 100 K–273 K and show a solid state phase change from triclinic to monoclinic between 175 K and 220 K without a conformational change. Graphical abstract: Highlights: Pentoses are converted to 1, 6, 9, 13-tetraoxadispiro(4.2.4.2)tetradecane in a single reactor. The crystalline product undergoes a phase change from triclinic to monoclinic between 175 K and 220 K. The Pd on silica-alumina catalyst can be reused at least three times. The product can be ring-opened to 1, 5-dihydroxy-2-pentanone.